Correction to: Innovative Microemulsion Loaded with Unusual Dimeric Flavonoids from Fridericia platyphylla (Cham.) L.G. Lohmann Roots (AAPS PharmSciTech, (2023), 24, 8, (212), 10.1208/s12249-023-02655-z) - do Nascimento, Jessyane Rodrigues [UNESP]; de Matos Monteiro Lira, Beatriz Santiago; do Nascimento, Matheus Oliveira; Lopes, Gláucia Laís Nunes; Ferreira, Glaucio Monteiro; de Souza Nunes, Glécilla Colombelli; Gonçalves, Renato Sonchini; Carvalho, André Luis Menezes; Vilegas, Wagner [UNESP]; da Rocha, Cláudia Quintino (Springer Nature, 2023)
The original article has been corrected. The author names Matheus Rodrigues has been updated to Matheus Oliveira do Nascimento, and Beatriz Santiago has been updated Beatriz Santiago de Matos Monteiro Lira.